Evaluasi penerapan prosedur penatausahaan bendahara pengeluaran dalam penerbitan Surat Perintah Pencairan Dana (SP2D) pada Badan Keuangan dan Aset Daerah Kota Manado - Najoan, Vricilia Febiola; Budiarso, Novi Swandari; Kapojos , Peter M. (Riset Akuntansi dan Portofolio Investasi, 2025)
The Expenditure Treasurer plays a strategic role in ensuring accountability and orderly management of regional finances, particularly in the issuance of Fund Disbursement Orders (SP2D). However, in practice, the SP2D issuance process often encounters administrative constraints that may hinder the timely implementation of regional government programs and activities. This study aims to evaluate the administrative procedures of the Expenditure Treasurer in issuing SP2D at the Regional Finance and Asset Agency (BKAD) of Manado City and to assess their compliance with the Regulation of the Minister of Home Affairs Number 77 of 2020. This study employs a qualitative research method with a case study approach, focusing on a single unit of analysis, namely BKAD Manado City. Data were collected through in-depth interviews with key informants involved in the SP2D issuance process and through document analysis related to regional financial administration. Data analysis was conducted using a descriptive qualitative approach by comparing actual practices with applicable regulatory provisions. The results indicate that, in general, the administrative procedures of the Expenditure Treasurer in issuing SP2D at BKAD Manado City have been implemented in accordance with the Regulation of the Minister of Home Affairs Number 77 of 2020. Nevertheless, several obstacles remain, particularly incomplete supporting documents and suboptimal inter-unit coordination, which contribute to delays in SP2D issuance. These findings highlight the importance of strengthening internal control mechanisms and improving administrative efficiency to enhance regional financial governance.